Epidemiology of inflammatory bowel disease-associated anemia in children and adolescents from 1990 to 2021: a global, regional analysis from the Global Burden of Disease Study - Xu, Chenjing; Mao, Xiaqiong; Xu, Ying; Cui, Xiufang (Frontiers in Pediatrics, 2025)
ObjectiveInflammatory bowel disease (IBD)-associated anemia cannot be ignored, as it can affect the growth and development of children and adolescents. This study aimed to report the global, regional, and national disease burden of IBD-associated anemia in children and adolescents.MethodsData on the prevalence of IBD-associated anemia and years lived with disability were obtained from the Global Burden of Disease Study 2021. Joinpoint regression analysis, age–period –ohort modeling analysis, and decomposition analysis were performed. Finally, an ARIMA model was established to predict the disease burden up to 2041.ResultsAnemia associated with IBD was most prevalent among adolescents aged 15–19 years, with significantly higher prevalence in females [11,487.26, 95% uncertainty interval (UI) = 8,826.54, 14,622.31] than in males (6,677.01, 95% UI = 5,179.56, 8,498.89). The age-standardized prevalence rate (ASPR) was highest in moderate anemia (17.5561, 95% UI = 14.9597, 20.8729). Joinpoint regression analysis suggested the ASPR of IBD-associated anemia in both males and females increased from 2005 to 2010 and then decreased after 2010. In the decomposition analysis, aging and population growth were the main drivers of changes in the prevalence of IBD-associated anemia. ASPR exhibits a fluctuating trend in males from 1990 to 2041 and is projected to remain stable in females from 2027 to 2041.ConclusionThe ASPR of IBD-associated anemia in children and adolescents increased from 2005 to 2010 and then decreased after reaching a peak in 2010. In the future, IBD-associated anemia will continue to pose a significant public health problem.